TECHNICAL AND ECONOMIC FOUNDATIONS FOR THE CONSTRUCTION AND RECONSTRUCTION OF ENTERPRISES PRODUCING CONSTRUCTION MATERIALS AND PRODUCTS (Spectrum Journal of Innovation, Reforms and Development, 2026)
The construction materials industry represents one of the key sectors of the national economy. The continuous growth of construction volumes, along with the increasing demand for energy-efficient and environmentally sustainable materials, necessitates the expansion and modernization of production capacities within this sector. The development of a feasibility study (technical and economic justification) is an essential stage in the construction and reconstruction of enterprises, as it enables a preliminary assessment of project efficiency and viability. This article examines the technical and economic foundations underlying the reconstruction and modernization of manufacturing enterprises.